Ensino e aprendizagem da argumentação por meio do gênero de texto comentário online da rede social instagram com alunos do 2° ano do ensino médio - Oliveira, Juliane Martins de (2025)
Writing development remains a challenge in the context of basic education. To face this challenge, research conducted within the Profletras program plays an important role in attempting to overcome it. For this study, we have chosen the online comment as a genre that can contribute to language learning and the development of stances in interactions within the digital context. This work aims to reflect on linguistic-discursive resources, especially argumentative connectors and modality markers, as important elements in the teaching and learning of argumentation. To this end, we analyze comments on the Instagram social network, considering them as a mega-instrument (Schneuwly and Dolz, 2004) in the teaching and learning of the Portuguese language. Our study is supported by a theoretical-methodological approach of Socio-discursive Interactionism (SDI) in relation to the concept of text genres, the textualization and enunciative mechanisms of Bronckart (1999), and Adam (2011) concerning argumentative connectors, as well as Paveau (2017/2021) regarding forms of techno - discourse. Regarding argumentation and point of view, we base our analysis on Plantin (2008), Amossy (2017, 2018, 2020), Cavalcante (2016), and Rabatel (2013, 2015, 2016), respectively. This is qualitative research employing the Action Research method (Thiollet, 1986). As a teaching device, we applied a Didactic Sequence (Schneuwly and Dolz, 2004) to teach argumentation, focusing especially on modality markers and argumentative connectors. Through the development of the Didactic Sequence, it is possible to observe an improvement in the students' argumentation, as well as better development of conscious thinking about topics requiring positioning, which contributed to the elaboration of points of view and arguments. Thus, we highlight the importance of a systematic teaching and learning approach aimed ataddressing current demands related to writing.